Analisis Keuntungan Usaha Kuliner Gorengan Di Kelurahan Girian Indah Kecamatan Girian Kota Bitung - Daniel Elsa Lomboan; Jenny Baroleh; Sherly G. Jocom (Sam Ratulangi University, 2022)
This study aims to determine and analyze the advantages of fried culinary business in Girian Indah Village, Girian District, Bitung City. The data used are primary data obtained from direct interviews with fried culinary entrepreneurs using questionnaires and secondary data obtained from journals and research reports taken from the internet. Sampling was carried out using the census method from a population of 4 carts selling fried foods: fried bananas, stuffed tofu, fried sweet potatoes, tempeh and bakwan. The results were analyzed by profit analysis followed by Revenue Cost Ratio (R/C-ratio). The results showed that this fried culinary business incurs an average total cost of one production (in 1 day) of Rp. 1,435,669 per day with an average income of Rp. 1,903,000 per day, and get an average total profit per business of Rp. 482,331 in one production/day. The result of R/C-Ratio of 1.31 which is greater than 1, means that this fried food business is profitable.